Rethinking narratives about youth experiencing homelessness: Exploring essential relationships and resilience. (April 2023) - Napoleon, Jenilee-Sarah; Evans, David W.; Weva, Vanessa K.; Francois, Tamarah; Namdari, Reyhane; Sherman, Jessica; Rimada, Camila M.; Morisseau, Nancy; Lafontant, Emmanuel; Miller, Sydney; Burack, Jacob A.
Abstract: To understand the factors promoting resilience among youth experiencing homelessness, we utilized a model of attachment security and explored the links among essential relationships with parents and peers, and the use of various socioecological resources contributing to resilience. 102 youth aged 16–24 (Mage = 20, SD = 2.07) were recruited from an organization servicing individuals in need. The Inventory of Parent and Peer Attachment was used to assess self-perceptions of relationships with parents and peers, and the Child and Youth Resilience Measure was used to assess engagement in resilience resources. Higher levels of attachment with parental figures were associated with increased engagement in seeking support from others (relational resilience), while higher levels of peer attachment were associated with higher levels of engagement in personal coping (individual resilience), such as locus of control, and of environmental resources (contextual resilience), such as the use of community and spiritual resources. Implications for practice are discussed.